(untitled) (Revista de Letras Norte@mentos, 2016)
MOLLICA, Maria Cecilia. PATUSCO, Cynthia. RIBEIRO BATISTA, Hadinei (Org.). Sujeitos em ambientes virtuais: Festschriften para Stella Maris Bortoni-Ricardo. São Paulo: Parábola Editorial, 2015. 149 p.